Improving Family, Carer and Community Professional Involvement in Patient Care for Individuals Admitted to a Psychiatric Intensive Care Unit - Kirsty Ward; Natasha Treagust; Suveera Prasad (BJPsych Open)
Aims: To assess and improve the consistency of family, carer and community team involvement in our MDT (multidisciplinary team) ward rounds on a PICU (Psychiatric Intensive Care Unit).